Poverty and economic development: Evidence for the Brazilian states - Luciano Nakabashi (EconomiA, 2018)
In the present study, our primary concern is to examine the effects of poverty on economic development across the Brazilian States from 1980 to 2015. Many studies assess the effects of economic growth and economic development on poverty incidence, but there is almost no one trying to measure the impact of poverty prevalence on economic development. The results of this paper indicate that poverty incidence is essential in the economic development of the Brazilian States. Poorer Brazilian States have lower income per worker even when controlling for investment in physical capital, human capital stock, and the effective depreciation of capital. The results point to the variables measuring extreme poverty as having more influence on the economic development of the Brazilian States in relation to the variables quantifying poverty.
Keywords: O11; O15; R58; C23; 330; Brazilian states; Economic development; Poverty incidence